PERAN PENDIDIKAN AGAMA ISLAM DALAM MEMBENTUK KARAKTER SISWA - Syah Rani Maha (Jurnal Penelitian Ilmu Pendidikan Indonesia, 2023)
Morals are behavior that is clearly visible, both in words and deeds, which is motivated by encouragement because of Allah. However, there are also many aspects related to attitudes or inner thoughts, such as initial morals which are related to various aspects, namely patterns of behavior towards God, fellow humans, and patterns of behavior towards nature. Moral issues become a barometer of a person's high or low status. This is in accordance with the words of the Prophet Muhammad SAW: "The most faithful people are those who have the best morals, and the best of you are those who have the best morals towards their wives." (H.R. Tirmidhi). The aim of this research is to develop students' morals to be better and to know the moral values instilled by PAI teachers by greeting before and after learning, being polite, gentle in speaking, respecting each other. In collecting this data, the author used classroom action research, as for the efforts made by PAI teachers to shape students' morals, namely by making efforts to habituate students. Keywords: Character, Adab, Islamic Religious Education